DEVELOPMENT OF THE ALGORITHM OF THE OPTIMAL VARIANT OF HUMAN FACE DETECTION - Naimov , Axadjon Tojimirzo ugli; Mavlonov, Sherzod Xasanboy ugli (INTERNATIONAL CONFERENCES, 2023)
This article discusses the development of the algorithm of the optimal variant of human face detection. The goal of human face detection is to locate and identify human faces in digital images or videos, which has a wide range of applications in various fields such as security systems, facial recognition, and human-computer interaction.